Implementasi Mengasihi Allah Sesuai Markus 12:30 Pada Mahasiswa Sekolah Tinggi Teologi Bethany Surabaya - Julianus Zaluchu (Jurnal Teologi dan Pelayanan Kerusso, 2018)
In this dissertation the researcher takes the title: Implementation Loves God In Mark 12:30 Among Students of Bethany High School Theology Surabaya. Students from Bethany High School Surabaya come from various backgrounds. This background colored the implementation and practice of loving God in Mark 12:30. In the field observation there is a negative phenomenon among students STT Bethany Surabaya in the implementation of loving God in Mark 12:30. In the formulation of the problem, the researcher determines from the four aspects of God's love in Mark 12:30, which aspect dominantly forms the implementation of loving God in the lives of STT Bethany Surabaya students. The temporary answer to the problem under investigation, whose truth needs to be tested empirically is the hypothesis. Based on the formulation of the problem, the study of the theory and framework of the above hypothetical proposed as follows: 1. Loving God with all the heart in Mark 12:30 among students STT Bethany tend to be in low to moderate position, 2. Loving God with all the soul in Mark 12:30 among the students of STT Bethany tends to be in low to moderate positions. 3. Loving God with all the intellect in Mark 12:30 among the students of STT Bethany tends to be on the way to high. 4. Loving God with all the strength in Mark 12:30 amongst the students of STT Bethany tends to be in a position of being heading high. The research methodology is quantitative with confirmatory explanatory approach that is based on quantitative in data collection and analysis to test the hypothesis specified. In this section of analysis and discussion of researchers conducted a discussion of the results of research hypotheses. The first hypothesis is that the application of the Y variable tends to be in a moderate position. The findings in the field regarding the application of variable Y are in a moderate position. The hypothesis is acceptable. Based on the results of statistical tests on the implementation of variable Y in the range of Lower Bound and Upper Bond value of 341.28 s / d 347.85 lies in the category is. Test the second hypothesis of implementation Loving God in Mark 12:30 among students STT Bethany the determining dimension is with all soul. The third hypothesis test is to love God in Mark 12:30 among students Bethany (Y) STT is in accordance with the hypothesis is from low to medium. Based on the above findings, the researcher proposes some practical implications that can be constructive input for STT Bethany Surabaya institution. The results of this study can be used by leaders and alumni STT Bethany to improve the quality of students in realizing loving God with all heart, soul, mind and strength.